High levels of circulating osteopontin in inflammatory lung disease regardless of SARS‐CoV‐2 infection. Issue 11 (8th November 2021) - Cappellano, Giuseppe; Abreu, Hugo; Raineri, Davide; Scotti, Lorenza; Castello, Luigi; Vaschetto, Rosanna; Chiocchetti, Annalisa
Abstract :